Antimicrobial Wound Dressings: A Concise Review for Clinicians - Faraz Yousefian; Roksana Hesari; Taylor Jensen; Sabine Obagi; Ala Rgeai; Giovanni Damiani; Christopher G. Bunick; Ayman Grada (MDPI AG, 2023)
Wound management represents a substantial clinical challenge due to the growing incidence of chronic skin wounds resulting from venous insufficiency, diabetes, and obesity, along with acute injuries and surgical wounds. The risk of infection, a key impediment to healing and a driver of increased morbidity and mortality, is a primary concern in wound care. Recently, antimicrobial dressings have emerged as a promising approach for bioburden control and wound healing. The selection of a suitable antimicrobial dressing depends on various parameters, including cost, wound type, local microbial burden and the location and condition of the wound. This review covers the different types of antimicrobial dressings, their modes of action, advantages, and drawbacks, thereby providing clinicians with the knowledge to optimize wound management.